Efeitos da depleção da micróglia na sensibilização comportamental e na preferência condicionada ao lugar induzidas por cocaína - Maria Carolina Machado Da Silva (2019)
INTRODUCTION: The use of recreational drugs can modify brain function by inducing changes in the reward system, mainly due to release of dopamine in the mesocorticolimbic pathway. Despite this, the etiopathogenesis of addiction is a much more complex process. Different data suggest that glial cells may participate in the drug addiction process, since they respond to neurochemical changes induced by the administration of these substances. OBJECTIVE: To test the hypothesis that microglia is related in behavioral changes induced by cocaine in behavioral sensitization and conditioned place preference tests. METHODS: Swiss mice aged 8-9 weeks were treated with the microglial depletor PLX3397 (40 mg/kg, p.o.) and submitted to behavioral sensitization or conditioned place preference induced by cocaine (15 mg/kg, i.p.). The treatment with PLX3397 lasted 7 or 9 days in the behavioral sensitization and conditioned place preference tests, respectively. Thereafter, the animals were euthanized and had their brain removed for analysis of number and morphology of Iba-1+ cells, and quantification of neurotrophic factors BDNF, NGF and GDNF on prefrontal cortex (PFC), hippocampus and striatum. RESULTS: Treatment with PLX3397 attenuated behavioral sensitization, but had no effect in the conditioned place preference induced by cocaine. In both cocaine or vehicle treated groups, PLX3397 reduced the number of Iba-1+ cells in nucleus accumbens core (NAcc), nucleus accumbens shell (NAcSh), and CA1 region of hippocampus. The drug also increased the rate of activation of Iba-1+ cells in NAcc and NAcSh in cocaine and vehicle groups. PLX3397 reversed the decrease in BDNF levels in PFC induced by cocaine, but not the NGF levels in striatum. In addition, animals treated with cocaine in combination with PLX3397 revealed a decrease in NGF levels in the hippocampus. Finally, cocaine, PLX3397, and the association of both drugs were able to decrease GDNF levels in the PFC. CONCLUSION: Considering the data of this study, we suggest that microglia participates in the pathological alterations that occur in neurobiology of addiction. The demonstration of the involvement of these cells in substance use disorders could open a new field for the development of new pharmacological treatments.